Percutaneous absorption of N,N-dimethylformamide in humans - Mráz, J; Nohová, H (International archives of occupational and environmental health, 1992)
Skin penetration fo N,N-dimethylformamide (DMF) liquid or vapour was studied in volunteers. Exposure to liquid DMF was performed in two ways: in a "dipping experiment", one hand was dipped up to the wrist in DMF for 2-20 min, while in a "patch experiment", 2 mmol DMF was applied to the skin and allowed to be absorbed completely. The period of exposure to DMF vapour (50 mg.m-3) was 4 h. The DMF metabolites N-hydroxymethyl-N-methylformamide ("MF"), N-hydroxymethylformamide ("F"), and N-acetyl-S-(N-methylcarbamoyl)cysteine (AMCC) were monitored in the urine. Liquid DMF was absorbed through the skin at a rate of 9.4 mg.cm-2.h-1. Percutaneous absorption of DMF vapour depended strongly on ambient temperature and humidity and accounted for 13%-36% of totally excreted "MF". The results suggest that skin absorption of liquid DMF is likely to contribute to occupational exposure substantially more than penetration of DMF vapour. The yield of metabolites after transdermal DMF absorption was only half of that seen after pulmonary absorption. Elimination of "MF" and "F" but not that of AMCC was delayed, which supports the contention that AMCC should be used instead of "MF" as the most suitable biomarker of DMF in cases where percutaneous intake can occur.
Keywords: Acetylcysteine; Male; Solvents; Dimethylformamide; rozpouštědla; acetylcystein; Adult; dospělí; mužské pohlaví; plyny; Gases; dimethylformamid; lidé; ženské pohlaví; Humans; kožní absorpce; formamidy; Formamides; Skin Absorption; Female; lidé středního věku; Middle Aged